The vanishing of the primary emission region in PKS 1510-089 - Aharonian, Felix A.; Ait Benkhali, Faical; Aschersleben, J.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, J.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, Konrad; Bi, B.; et al. (The astrophysical journal. Part 2, Letters, 2023)
In 2021 July, PKS 1510−089 exhibited a significant flux drop in the high-energy γ-ray (by a factor 10) and optical (by a factor 5) bands and remained in this low state throughout 2022. Similarly, the optical polarization in the source vanished, resulting in the optical spectrum being fully explained through the steady flux of the accretion disk and the broad-line region. Unlike the aforementioned bands, the very-high-energy γ-ray and X-ray fluxes did not exhibit a significant flux drop from year to year. This suggests that the steady-state very-high-energy γ-ray and X-ray fluxes originate from a different emission region than the vanished parts of the high-energy γ-ray and optical jet fluxes. The latter component has disappeared through either a swing of the jet away from the line of sight or a significant drop in the photon production efficiency of the jet close to the black hole. Either change could become visible in high-resolution radio images.
Gesehen am 28.03.2024